Decision making in local government: the myth of success model of information system - Mohamed Sawal, Mohd Zool Hilmie (2016)
A good decision must be able to deliver a good result to the community and overcome the problem.Relating with local government it’s reflecting their services serving to their community.Thus, the role of information system plays a major role in providing good data to the decision maker.In reality, some decision maker does not want to use or accept the information system.This paper proposed the conceptual model in understanding the acceptance of information system. Two models Delone & McLean Information System Success 2003 and Unified Theory of Acceptance and Use of Technology (UTAUT) are being discussed.